TRI KAYA PARISUDHA SEBAGAI LANDASAN KOMUNIKASI PENDIDIKAN DALAM MODERASI BERAGAMA - Yhani, Putu Cory Chandra (Satya Widya: Jurnal Studi Agama, 2022)
People's interactions, which are now being eroded in a superficial ideology, create conflicts between religions, ethnicities, and races. The deepening of the science of public communication education is now defeated by social media issues whose truth can be doubted. It occurred to the government's mind to maintain the harmonization of the people in caring for a diversity in a moderation system. To produce valid and reliable data, this research uses qualitative research methods. To produce logical data, this article performs several stages Related references really support the validity of a scientific work, therefore library techniques are also used through literature exploration on Google Scholar. The Hindu concept contained in the Vedic teaching provides an understanding of harmony, which is contained in Tri Kaya Parisudha, that it is important to maintain harmony in order to minimize conflicts that have occurred recently. Tri Kaya Parisudha teaches that being a society must think, have good morals, and behave properly, so that harmony will bind one another.